Implementasi Program Muhadharah untuk Meningkatkan Karakter Disiplin dan Kreatif Peserta Didik Pondok Pesantren Salafiyah Wustho Hasan Munadi - Binti Rofii'ah; Redha Nurain; Mariati Masthuroh; Lailatul Sangadah; Firroh Tanisya Marsasna; Nurul Eka Aprillia (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Indiscipline, low self-confidence, and limited creativity remain critical challenges in character education within Islamic boarding schools, requiring structured programs that can strengthen students’ moral, communicative, and creative capacities. This study aims to analyze the implementation of the Muhadharah Program in improving students’ disciplinary and creative character at Pondok Pesantren Salafiyah Wustho Hasan Munadi Ponorogo, examine its role in character formation, and identify the supporting and inhibiting factors affecting its implementation. This research employed a descriptive qualitative approach with a field research design. Data were collected through semi-structured interviews, direct observations, and documentation involving school leaders, teachers, program supervisors, and students. The data were analyzed through coding, data presentation, and conclusion drawing, with triangulation used to strengthen data validity. The findings show that the Muhadharah Program is implemented as a compulsory flagship activity conducted every Saturday through a rotating class-based schedule. The program fosters students’ discipline through punctuality, task responsibility, preparation, and compliance with activity procedures, while creativity is developed through speech writing, public speaking practice, language variation, storytelling, and expressive delivery. Supporting factors include competent educators, consistent program implementation, a conducive pesantren environment, students’ internal motivation, and adequate facilities, whereas inhibiting factors include low student interest, shyness, limited time allocation, monotonous learning habits, and insufficient creativity-oriented support. The study implies that a structured and sustainable Muhadharah Program can serve as a practical character education model for Islamic educational institutions in strengthening students’ discipline, creativity, confidence, and communication skills.